Applications of a radioimmunoassay technique to the study of luteinizing hormone secretion in the rat - Querido, David (Division of Medical Biochemistry, 2020)
A sensitive and reproducible double antibody radioimmunoassay technique, requiring 50ul of unknown serum or plasma per assay tube, is described for use with 125I and rabbit anti-rat LH serum. The assay system was applied to the study of LH secretion in rats under both normal and experimentally manipulated conditions. Particular attention was focussed upon comparison of circulating LH levels in conscious, unstressed animals with those in anaesthetized animals, with or without surgical stress. Thereafter, the effects of acoustic stimulation and of exogenous LRH administration were studied in conscious and anaesthetized animals. Urethane anaesthesia exerted a profound effect upon the LR-secretory response to exogenous LRH in male rats. Available evidence suggests that the blood sampling method, surgical stress and anaesthesia are each capable of significantly influencing LH secretion, thereby emphasizing the value of studies using conscious, unstressed animals. While a direct effect of urethane on the pituitary gland cannot be excluded, attention is drawn to the possible mediation of a urethane-sensitive inhibitory influence in the mechanism controlling LH secretion in the rat.